Utilization of Digital Technology in Improving Economic Literacy for Low Income Communities - Falyuhsin, Falyuhsin; Gunawan, Hendra (Jurnal Transformasi Digital dalam Ekonomi, Bisnis, dan Manajemen, 2025)
This study aims to analyze the use of digital technology in improving economic literacy among low-income communities. Low economic literacy can be a barrier for people in personal financial management, family economic planning and participation in economic activities. Digital technologies, especially economic education apps, have the potential to address this issue by providing easier access to information and educational resources. This study uses a mixed method, combining qualitative and quantitative approaches, to evaluate the effect of digital technology on improving economic literacy. The results show that the use of economic education apps can improve economic literacy by 22.6% among low-income communities. However, obstacles such as limited internet access and difficulties in understanding more complex materials remain a challenge. Based on these findings, it is recommended to improve access to digital technology, simplify economic education materials, and develop digital literacy training programs. This research contributes to the understanding of how digital technology can be used to improve the economic well-being of low-income communities by providing practical recommendations for further development. Potential follow-up research includes long-term studies to evaluate the sustainability impact of economic education applications on people's financial behavior and well-being.